HOW THE SOCIAL PSYCHOLOGIST GOT HIS FACTS: A POSTCOLONIAL TALE - Collins, Anthony (PINS-Psychology in Society, 2026)
What follows is a script for a video, prefaced with an explanation, which was developed as the opening lecture of an introductory course in Social Psychology. The aim of the video was to destabilise the ways in which Social Psychology is imported and marketed as an authoritative body of knowledge, without reflection on the problems and limitations it might face in being implemented in local contexts. As explained in the preface, the strategy chosen was not to contest the arguments and findings of Social Psychology, but rather to subvert its method of self-presentation. Hence the video is a children’s fable, a postcolonial "Just-So" story, this time told by the native, about the process of colonisation by the western academy.